Palm-Sorbent: Acid-Impregnated Palm Fibre for Sorption of Cr (VI) from Chrome Plating Effluent - Naimah, Ibrahim; Umi Fazara, Md. Ali; Masitah, Hasan; Mahyun, Ab Wahab; Salwa, Mohd Zaini Makhtar; Nazerry Rosmady, Rahmat; Razi, Ahmad (Malaysian Invention and Design Society (MINDS), 2010)
Naimah Ibrahim and her team won silver for Palm-Sorbent: Acid-Impregnated Palm Fibre for Sorption of Cr (VI) from Chrome Plating Effluent. ITEX 2007, 18th - 20th May 2007 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.